A Web-Based Escape Room to Raise Awareness About Severe Mental Illness Among University Students: Randomized Controlled Trial - Jose M Rodriguez-Ferrer; Ana Manzano-León; Adolfo J Cangas; Jose M Aguilar-Parra (JMIR Publications, 2022)
BackgroundPeople with severe mental illness (SMI) face discriminatory situations because of prejudice toward them, even among health care personnel. Escape rooms can be a novel educational strategy for learning about and empathizing with SMI, thus reducing stigma among health care students. ObjectiveThis study aimed to examine the effect of the Without Memories escape room on nursing students' stigma against SMI. MethodsA pre- and postintervention study was conducted with a control group and an experimental group. A total of 306 students from 2 Andalusian universities participated in the study. Data were collected through a pre-post study questionnaire, consisting of an adapted version of the Attributional Style Questionnaire and a questionnaire on motivation for cooperative playful learning strategies. The control group carried out an escape room scenario without sensitizing content, whereas the experimental group carried out an escape room scenario on SMI, with both escape rooms being carried out in a 1-hour session of subjects related to mental health. To answer the research questions, a 2-way analysis of variance with repeated measures, a linear regression, and a 2-way analysis of variance were performed. ResultsAfter the intervention, a significant reduction (P<.001) was observed in the experimental group in stigmatizing attitudes compared with the control group, in which no statistically significant changes (P>.05) were observed. In contrast, the linear regression (t195=−22.15; P<.001) showed that there was an inverse relationship between flow and the level of reduced stigma. When controlling for having or not having a close relative, the intervention was also shown to be effective (P<.001) in reducing the stigma displayed, both for people with affected and unaffected relatives. ConclusionsOur findings suggest that the Without Memories escape room can be used as an effective tool to educate and raise awareness about stigmatizing attitudes toward SMI in university students studying health care. Future testing of the effectiveness of educational escape rooms should be designed with new programs through playful strategies of longer duration to evaluate whether they can achieve a greater impact on motivation, acquisition of knowledge, and awareness. In addition, the feasibility of implementing the Without Memories escape room in other careers related to health and community should be investigated.